2009
DOI: 10.1071/ah090117
|View full text |Cite
|
Sign up to set email alerts
|

Local trends in emergency department attendances by older patients in an ageing national population

Abstract: Nursing-led aged care services were set up at our Emergency Department (ED) in 2004-05 to assist in the appropriate discharge of older patients. This study examined local trends in ED attendances by older patients. A retrospective study was conducted at an inner-city adult ED in a region with a 2.2% annual growth rate. Patient demographics, Australasian Triage Scale (ATS) category and admission/discharge status were collected from January 2002 to December 2006. Total ED attendances increased 7.7% from 66 687 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Older adults from ACFs have longer waits (average six hours) in the ED before being admitted or discharged (Crilly et al 2008). In a nearby ED, older adults requiring admission were found to have longer ED LOS than those being discharged from the ED (7AE0 vs. 3AE4 hours) during the same time period of this study (Chu et al 2009). The longer ED LOS (7AE5 hours) for HINH patients in our study possibly reflects the additional time HINH patients spent waiting in the ED (having been admitted to the ED observation ward) for HINH review and transport back to the ACF to have care continued.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Older adults from ACFs have longer waits (average six hours) in the ED before being admitted or discharged (Crilly et al 2008). In a nearby ED, older adults requiring admission were found to have longer ED LOS than those being discharged from the ED (7AE0 vs. 3AE4 hours) during the same time period of this study (Chu et al 2009). The longer ED LOS (7AE5 hours) for HINH patients in our study possibly reflects the additional time HINH patients spent waiting in the ED (having been admitted to the ED observation ward) for HINH review and transport back to the ACF to have care continued.…”
Section: Discussionsupporting
confidence: 52%
“…2008). In a nearby ED, older adults requiring admission were found to have longer ED LOS than those being discharged from the ED (7·0 vs. 3·4 hours) during the same time period of this study (Chu et al. 2009).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…42 Therefore, if using the finding of the present study to inform local policy and planning, it would be necessary to explore specific local trends.…”
Section: Limitationsmentioning
confidence: 99%
“…Most authors have considered age-associated patterns and reached a range of conclusions. McConnel and Wilson (1998) and Lowthian et al (2011a) found that demand for EMS services increased exponentially with age, and Chu et al (2009) observed a relative decrease in ED attendance by patients 65 and older across certain triage groups. Interestingly, Lowthian et al (2011b) proved that although demand for ambulances was growing faster that can be explained by population growth, it was possible to attribute only 25% of the EMS calls to ageing and population growth.…”
Section: Literature Reviewmentioning
confidence: 95%